ESTABLISHMENT AND PLANNING OF ECONOMIC DESTINATIONS THROUGH FINANCIAL FEASIBILITY APPROACH TO BITING BUSINESS (STUUK SATE) IN MALANG REGENCY - Putra Irwandi; Mangku Purnomo; Sugeng Riyanto; Vi’in Ayu Pertiwi (Agricultural Socio-Economics Journal, 2023)
Financial feasibility analysis related to the formation of economic destinations is carried out to formulate the required information related to resources, costs, benefits, and feasibility by what is proposed and expected. This research was conducted to determine business estimation and planning for establishing economic destinations in Malang Regency. This study uses the mixed method, namely collecting information qualitatively related to the skewer-biting business unit and quantitatively calculating the skewer-biting business's feasibility in an estimated period of 20 years. This research was conducted purposively to biting business owners in Malang Regency. Data collection was carried out by observation, interviews, documentation, and feasibility calculations. Based on the results of the analysis, it was found that within 20 years, the formation of economic destinations can be formed with the value of each eligibility consisting of a positive NPV of IDR 988,153,018, BCR has a value of > 1 which is 2.04, IRR shows a value of 23% , and a payback period of 7 years during implementation.